Energy Storage: Superior Potassium Ion Storage via Vertical MoS2 "Nano‐Rose" with Expanded Interlayers on Graphene (Small 42/2017). Issue 42 (8th November 2017) - Xie, Keyu; Yuan, Kai; Li, Xin; Lu, Wei; Shen, Chao; Liang, Chenglu; Vajtai, Robert; Ajayan, Pulickel; Wei, Bingqing
Abstract : In article number1701471, Keyu Xie, Bingqing Wei, and co‐workers synthesize molybdenum disulfide (MoS2 ) "roses" grown on reduced graphene oxide sheets (rGO) with a unique nano‐architecture. It displays one of the best electrochemical performances to date as an anode material for nonaqueous K–ion batteries (KIBs), and a combined K + storage mechanism of intercalation and conversion reaction is revealed. Important insights and understanding of advanced KIBs are provided, opening new opportunities for developing less‐expensive and more efficient next‐generation electrochemical energy storage devices.